2012
DOI: 10.1002/pmh.1218
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating normal and disordered personality using the General Assessment of Personality Disorder (GAPD)

Abstract: Criteria to differentiate personality disorder from extremes of normal personality variations are important given growing interest in dimensional classification because an extreme level of a personality dimension does not necessarily indicate disorder. The DSM-5 proposed classification of personality disorder offers a definition of general personality disorder based on chronic interpersonal and self/identity pathology. The ability of this approach to differentiate personality disorder from other mental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Self-interpersonal problems such as insecure attachment and maladaptive schemas have been shown to be associated significantly with personality disorder psychopathology and impairments in psychosocial functioning in general, as well as to affect treatment alliance and outcome (e.g., [24][25][26][27][28][29][30][31][32][33][34]. Furthermore, self pathology has been shown to have incremental validity over interpersonal pathology in predicting overall severity of personality pathology (35), so both components are represented in the DSM-5 Level of Personality Functioning Scale.…”
Section: Clinical Utilitymentioning
confidence: 97%
“…Self-interpersonal problems such as insecure attachment and maladaptive schemas have been shown to be associated significantly with personality disorder psychopathology and impairments in psychosocial functioning in general, as well as to affect treatment alliance and outcome (e.g., [24][25][26][27][28][29][30][31][32][33][34]. Furthermore, self pathology has been shown to have incremental validity over interpersonal pathology in predicting overall severity of personality pathology (35), so both components are represented in the DSM-5 Level of Personality Functioning Scale.…”
Section: Clinical Utilitymentioning
confidence: 97%
“…As illustrated in Figure 1, in both PD groups (with and without depression), the mean score on the subscale LMPD was 3.4 (SD = 0.9 and 1.0, resp.). Normative comparison showed that this score is in the 95th through 100th percentile (very high) of a normal population group, 25 as was the case for non-PD patients with depression, with a mean score of 3.1 (SD = 1.1) and for the non-PD patients without depression with a mean score of 2.7 (SD = 1.1). For normal controls, the mean score was 1.6 (SD = 0.6), which is consistent with the 20th through 80th percentile Meaning in life as a facet of personality functioning in personality disorder (average) of a normal population group.…”
Section: Meaning Direction and Purpose In Life Among The Five Groupsmentioning
confidence: 77%
“…the General Assessment of PD (GAPD)) . For low self‐directedness, the GAPD distinguishes three subscales: (1) lack of autonomy and agency, (2) LMPD in life and (3) difficulty setting and attaining rewarding goals . The second subscale, LMPD, is relevant for the present study and contains items that are similar to other meaning‐in‐life self‐report questionnaires, such as the Purpose in Life scale, the Life Regard Index or the Meaning in Life Questionnaire …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation